Activated glia cells cause bioenergetic impairment of neurons that can be rescued by knock-down of the mitochondrial calcium uniporter - Casaril, Angela Maria; Katsalifis, Athanasios; Schmidt, Rolf; Bas Orth, Carlos (Biochemical and biophysical research communications, 2022)
Neuroinflammation is a hallmark of various neurological disorders including autoimmune-, neurodegenerative and neuropsychiatric diseases. In neuroinflammation, activated microglia and astrocytes release soluble mediators such as cytokines, glutamate, and reactive oxygen species that negatively affect neuronal function and viability, and thus contribute to neurodegeneration during disease progression. Therefore, the development of neuroprotective strategies might be important in addition to treating inflammation in these diseases. Mitochondria are promising cellular targets for neuroprotective interventions: They are among the first structures affected in many neuroinflammatory diseases, with mitochondrial impairment ranging from impaired respiratory activity and reduced mitochondrial membrane potential to mitochondrial oxidation and fragmentation. Therefore, we developed a cell culture model that resembles an early state of inflammation-induced neuronal mitochondrial dysfunction preceding neuronal cell death, and can be used to test mito- and neuroprotective strategies. Rat primary cortical neurons were challenged with conditioned medium from mixed primary cultures of rat microglia and astrocytes that had been activated with lipopolysaccharide and ATP. When sublethal amounts of glia-conditioned medium were added to neurons for 24 h, mitochondrial membrane potential and ATP levels were decreased, whereas mitochondrial redox state remained unaffected. Effects on mitochondrial membrane potential and ATP levels were ameliorated by knock-down of the mitochondrial calcium uniporter in neurons. This study suggests that neuronal bioenergetic failure is an early event during neuroinflammation and it identifies the mitochondrial calcium uniporter as a candidate target for neuroprotection in this context.